My hero academia vigilantes. 10 - Furuhashi, Hideyuki, 1971-; Horikoshi, Kōhei, 1986- (Shonen Jump manga., 2021)
"Pop has emerged as the new Queen Bee, her transformation forced upon her by the villainous Nomura, a.k.a. Number 6. At his direction, Pop begins to rain destruction down on Naruhata. With a villain on the loose, it's only natural for heroes to be called in to deal with the situation, but Koichi knows his friend's life and soul are at stake. Will inspiration from his old master and training with past foes help him find the hero within?"--